Architecture and Visual Privacy in Islam: Comparative Analysis of Hausa and Malay Traditional Houses - Abdulkarim Aliyu, Aisha; Sabrina Ismail, Alice; Aminu Dodo, Yakubu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Housing is a multi-faceted issue and fundamental to the well-being, survival, and health of human beings, transcending their mere physicality as shelters to assume a profound role in safeguarding the privacy of their inhabitants. This research endeavour seeks to conduct a comparative analysis and exploration of the mechanisms governing visual privacy within two distinct cultural contexts: the traditional Hausa housing of Nigeria and the traditional Malay housing of Malaysia. To provide privacy, visual components of the idea of "seeing but not being seen" are essential. Using a research approach based on in-depth case studies that include careful observations, this investigation reveals a common feature that exists in both cultural situations. Irrespective of variations in dwelling size, these traditional houses emerge as adept providers of visual privacy. Notably, this is achieved without compromising the ethos of community intimacy, social interactions, and the intrinsic warmth of hospitality. It is envisaged that this research will serve as an enlightening exploration into the intricate paradigms of visual privacy, shedding light on the nuances of regulation within the traditional housing of both the Hausa and Malay communities.